Differential distribution of microsatellite allele frequencies in Koompassia malaccensis of contrasting habitat preferences - Lee, Chai Ting; Lee, Soon Leong; Qamaruz Zaman, Faridah; Siraj, Siti Shapor; Ng, Kevin Kit Siong; Muhammad, Norwati (2009)
Not many tropical plant species growing on dry soil can thrive in the peat swamp habitat, Koompassia malaccensis is among the unique species. Koompassia malaccensis, or locally known as kempas, is one of the major commercial timber species in Southeast Asia. It has been the interest of ecologists to know whether K. malaccensis found in the peat swamp and dry land are genetically distinct or their existence in such contrasting habitats is merely due to phenotypic plasticity. Findings from a population genetic study of K. malaccensis in 34 natural populations throughout Peninsular Malaysia revealed presence of ecotypic differentiation. A total of 20 microsatellite loci were analysed with an average of 29 samples per population. In the majority of the loci studied, a consistent trend was observed in the distribution of allele frequencies among the populations, in that the peat-swamp (Kuala Langat Selatan and Pekan) and non-peat-swamp populations shared different common alleles. In loci Kma057, Kma163 and Kma172a, the predominant alleles in the peat-swamp populations were either absent or in low frequencies (≤ 0.115) in the non-peat-swamp populations and vice versa. The significant divergence of allele frequencies at nuclear loci indicates that these two ecotypes are most likely of different evolutionarily significant units (ESUs).